Factor Affecting Preoperative Anxiety of Orthopedic Surgery Patients - Chinnoros, Somporn; Boriboonthanakul, Valaiporn (Journal of health and health management, 2022)
This research is a cross-sectional study. Objective to study preoperative anxiety and factors affecting preoperative anxiety of orthopedic surgery patients. The purposive sample was 140 of orthopedic surgery patients at a hospital in Bangkok. The research instrument was a personal data record form, Amsterdam Preoperative Information Scale. This study was analyzed using descriptive statistics, and multiple regression analysis. The finding revealed that the sample had a high level of overall preoperative anxiety ( = 4.08, SD = 0.83). Age, need for information, and history of surgery were affecting with preoperative anxiety. And gender was not affecting with preoperative anxiety. Suggestion: The sample had a high level of overall preoperative anxiety. Nurse should help to relieve preoperative anxiety with give the information about surgery or anesthesia to the patient